Ecological significance of pollinators in biodiversity conservation (Zoological Records and Reviews, 2023)
Pollinators -- primarily wild bees, hoverflies, butterflies, moths, and beetles -- provide essential ecosystem services thatunderpin both the reproductive success of wild plant communities and the productivity of agricultural systems, whilethemselves depending on the floral diversity, nesting resources, and landscape connectivity that biodiversityconservation maintains. This mutualistic interdependence makes pollinators both ecological cornerstones and sensitiveindicators of ecosystem health. This review synthesises evidence from 204 primary studies (2005-2023) examining theecological roles of pollinators in European biodiversity conservation, evaluating four interconnected dimensions:pollinator contributions to wild plant reproductive success and community assembly, pollinator population trends anddrivers of decline, pollinator-plant network structure and robustness, and conservation management approaches forpollinator-inclusive landscape management. Wild bees provide pollination services to 84% of European flowering plantspecies and are implicated in the reproductive success of 78% of European crop species. European wild bee diversityhas declined by an estimated 37% over 1980-2020 based on Red List assessments, with agricultural intensification(pesticides, habitat loss, floral resource reduction) as the primary driver in 82% of assessed declining species.Pollinator-plant interaction networks show functional redundancy in most European systems but are vulnerable to theloss of specialist interaction links in simplified agricultural landscapes. Habitat management interventions --agri-environment wildflower strips, hedgerow restoration, reduced mowing frequency -- increase pollinator abundance by48-148% in paired comparison studies. Implications for the EU Pollinators Initiative, Common Agricultural Policyagri-environment scheme design, and Nature Restoration Law agricultural ecosystem restoration targets are discussed.
Keywords: floral resources; ecosystem services; wildflower strips; EU Pollinators Initiative; agri-environment schemes; agricultural intensification; plant-pollinator networks; biodiversity conservation; wild bees; pollinators